An Overview of Artificial Intelligence (AI) in 6G: Types, Advantages, Challenges and Recent Applications - Abdullah M. Al-Ansi; Ahmed Al-Ansi (Universitas Ahmad Dahlan, 2023)
The world is on the cusp of a new communications revolution. The next generation of communication networks, known as 6G, will enable a wide range of new applications and services that are not possible with current 4G or 5G networks. In overview, we will review Artificial Intelligence (AI) Types, Advantages, challenges and some of the most promising applications of 6G technology. Some of the key applications that are being developed for 6G communication networks include Digital Twin (DT), Holograms, Robot Avatar, High Density (IoT), and AR & VR. The use of these applications in 6G communication networks is not a new concept, but integration to 6G will need more improvements. These applications have been around for some time now and have seen various improvements over the years. However, with the advent of 6G communication networks, the use of AR and VR is expected to see a drastic change. This paper contributes to the existing literature about the nature of 6G and applications to give more understanding and further discussion in potential and new trends.